Alternative Conceptions about Micro-organisms are Influenced by Experiences with Disease in Children. Issue 1 (2nd January 2016) - Prokop, Pavol; Fančovičová, Jana; Krajčovičová, Adriána
Abstract : Children's ideas concerning natural phenomena often differ from those of scientists, and these ideas are termed as alternative conceptions. The prevalence of alternative conceptions is highest among young children who possess less experience with the natural world as compared with adults. Children's ideas about micro-organisms are of special importance, because an improved awareness of them may reduce risk of contamination by pathogenic infection. We investigate in this paper how individual differences in vulnerability to disease influence expressions of conceptions regarding micro-organisms amongst kindergarten children. More disease-vulnerable children drew smaller micro-organisms and used darker colours when drawing them compared to their healthier counterparts. The children's drawings were not influenced by gender differences. Interviews showed that all the children knew that micro-organisms are somewhere in the human body and that their placement in all probability reflects their own experiences with disease. Perhaps surprisingly, hands were one of the least frequently cited sources of micro-organisms which may reflect low awareness on the part of children regarding threats from potentially pathogenic bacteria. These results support the universality of children's conceptions regarding micro-organisms and suggest further implications both for teaching and research regarding children's conceptions.